2016
DOI: 10.1016/j.jhep.2015.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte exosomes mediate liver repair and regeneration via sphingosine-1-phosphate

Abstract: Background & Aims Exosomes are small membrane vesicles involved in intercellular communication. Hepatocytes are known to release exosomes, but little is known about their biological function. We sought to determine if exosomes derived from hepatocytes contribute to liver repair and regeneration after injury. Methods Exosomes derived from primary murine hepatocytes were isolated and characterized biochemically and biophysically. Using cultures of primary hepatocytes, we tested whether hepatocyte exosomes indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
215
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(224 citation statements)
references
References 34 publications
7
215
2
Order By: Relevance
“…3C). Other extracellular matrix (ECM) proteins have been reported within exosomes (44,45). To examine whether other ECM proteins could be responsible for integrin activation by exosomes, we blotted lysed exosomes for collagen I, which was not detected in our serum-derived exosomes.…”
Section: Fn-integrin Interactions Contribute To Exosome Adhesion Andmentioning
confidence: 96%
“…3C). Other extracellular matrix (ECM) proteins have been reported within exosomes (44,45). To examine whether other ECM proteins could be responsible for integrin activation by exosomes, we blotted lysed exosomes for collagen I, which was not detected in our serum-derived exosomes.…”
Section: Fn-integrin Interactions Contribute To Exosome Adhesion Andmentioning
confidence: 96%
“…EVs are a route for cell-derived cargo to be shed from cells, and a mechanism for delivery of specifi c cargoes from donor cells to recipient cells, thus acting as carriers of a stress-stimulated message. Recently, studies have demonstrated an increase in circulating EV release under in vitro lipotoxic conditions, circulating EVs in mouse models of NASH and ischemia/reperfusion injury, and in patients with chronic hepatitis C and NASH (11)(12)(13). Furthermore, it has been reported that ceramides are needed for the formation of EVs via the multivesicular body (MVB) endosomal traffi cking pathway ( 14 ).…”
Section: Nanoparticle Tracking Analysismentioning
confidence: 99%
“…Hiroyuki et al discovered that exosomes derived from hepatocytes can promote the proliferation and regeneration of liver tissue both in vitro and in mice models of liver ischemia/reperfusion injury or partial hepatectomy (22). The researchers believed that the underlying mechanism involves sphingosine 1-phosphate (S1P).…”
Section: Exosomes In Liver Physiology and Pathology Processesmentioning
confidence: 99%
“…The researchers believed that the underlying mechanism involves sphingosine 1-phosphate (S1P). Hepatocyte-derived exosomes carrying neutral ceramidase and sphingosine kinase 2 (SK2) are captured by adjacent hepatocytes and raise the intracellular level of sphingosine-1-phosphate, thus promoting hepatocyte proliferation (22).…”
Section: Exosomes In Liver Physiology and Pathology Processesmentioning
confidence: 99%